Feasibility and efficacy of an acceptance and mindfulness-based group intervention for young people with early psychosis (Feel-Good group) - von Hardenberg, Laura; Leopold, Karolina; Stenzel, Nikola; Kallenbach, Michèle; Aliakbari, Navid; Bechdolf, Andreas; Mehl, Stephanie (Frontiers in Psychiatry, 2022)
Background: Over the last decade, researchers have sought for alternative interventions that have better treatment effects than cognitive behavioral therapy (CBT) when treating psychotic symptoms. Mindfulness-based interventions have been a proposed alternative to CBT, yet research regarding its feasibility, acceptance and effectiveness is lacking when treating individuals with early psychosis in inpatient settings. Objective: Before conducting a large-scale randomized controlled trial (RCT), this pilot study evaluated the feasibility and the potential efficacy of a mindfulness-based inpatient group intervention that targets emotion regulation in patients with early psychosis, and thus indirectly improving psychotic symptoms. Methods: A pre-post study was performed. Thirty-six patients with early psychosis treated at the specialized inpatient treatment “Frühinterventions- und Therapiezentrum; FRITZ” (early intervention and therapy center) received eight group therapy sessions. Assessments were performed at baseline, after 8 weeks post treatment and at Follow-Up after 16 weeks. Results: Rates of patients who participated in the study suggests that a mindfulness-based group therapy is highly accepted and feasible for patients with early psychosis being treated in an inpatient ward. Friedman analyses revealed significant changes in the primary outcomes of emotional goal attainment (Goal 1: W = .79; Goal 2: W = .71) and psychotic symptoms (PANSS-T: W = .74). Significant, albeit small, effect sizes were found in patients’ self-perception of emotion regulation skills (ERSQ: W = .23). Discussion: We found favorable findings regarding the feasibility and acceptance of the Feel-Good mindfulness-based intervention. Results of the study provide a basis for an estimation of an adequate sample size for a fully-powered RCT that needs to be conducted to test whether Feel-Good is effective in the inpatient treatment of psychotic symptoms for individuals with early psychosis. Trial Registration: NCT04592042. Available at: https://clinicaltrials.gov/ct2/show/NCT04592042